2015
DOI: 10.1186/s12885-015-1176-2
|View full text |Cite
|
Sign up to set email alerts
|

No significant viral transcription detected in whole breast cancer transcriptomes

Abstract: BackgroundStudies evaluating the presence of viral sequences in breast cancer (BC), including various strains of human papillomavirus and human herpes virus, have yielded conflicting results. Most were based on RT-PCR and in situ hybridization.MethodsIn this report we searched for expressed viral sequences in 58 BC transcriptomes using five distinct in silico methods. In addition, we complemented our RNA sequencing results with exome sequencing, PCR and immunohistochemistry (IHC) analyses. A control sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
2
10
1
Order By: Relevance
“…Tumor-specific truncating LTAg mutations were not detected in mapped viral reads from these two tumors. Although this finding is of uncertain significance, the much lower number of viral reads in these two samples suggests background low level viral loads previously reported in non-MCC carcinoma, possibly representing background wild-type viral infection (19). Based on negative qPCR and immunohistochemistry, these tumors were categorized as MCPyV-negative.…”
Section: Resultsmentioning
confidence: 53%
“…Tumor-specific truncating LTAg mutations were not detected in mapped viral reads from these two tumors. Although this finding is of uncertain significance, the much lower number of viral reads in these two samples suggests background low level viral loads previously reported in non-MCC carcinoma, possibly representing background wild-type viral infection (19). Based on negative qPCR and immunohistochemistry, these tumors were categorized as MCPyV-negative.…”
Section: Resultsmentioning
confidence: 53%
“…given BLVs role in bovine B cell leukaemia); and exome sequencing and RNAseq of breast cancer FFPE samples from Belgium also found no evidence of BLV or other retroviruses [11]. Conversely, a multi-pathogen probe-based array found evidence of retroviruses in a proportion of screened FFPE breast cancer samples [12], as well as other viral and bacterial pathogens.…”
Section: Htlvmentioning
confidence: 95%
“…As a result, since the mid-1990s studies have used primers complementary to regions of the MMTV genome with low homology to known HERVs, commonly targeted to the env region of MMTV which has just 16% homology to HERVK-10, the most closely related HERV. A recent systematic review of these refined molecular studies concluded that, while many studies detected MMTV env sequences in malignant tissue, various methodological flaws meant that none of the studies with a positive result were convincing[16].Fimereli et al harnessed multiple in silico techniques to analyse breast cancertranscriptomes for viral gene expression, and concluded that no viruses were expressed highly enough to be considered causative, furthermore MMTV-like sequences were not detected[11]. As discussed above, RNAseq and deep sequencing studies of breast cancer samples have produced mixed support for the presence of a retrovirus in human breast cancer.…”
mentioning
confidence: 99%
“…Using this approach it has been possible to identify a novel virus in organ transplant recipients 16 , HPV in squamous cell carcinoma of the head and neck 17 , hepatitis B virus in hepatocellular carcinoma 18 and Epstein Barr virus in gastric carcinoma 17 . However, to date, NGS approaches have failed to detect the expression of viral RNA (transcripts) in breast adenocarcinoma 17 19 20 . Moreover, only one study has examined whether a breast cancer sample that is positive for HPV DNA is also positive for HPV transcript 19 .…”
mentioning
confidence: 99%
“…However, to date, NGS approaches have failed to detect the expression of viral RNA (transcripts) in breast adenocarcinoma 17 19 20 . Moreover, only one study has examined whether a breast cancer sample that is positive for HPV DNA is also positive for HPV transcript 19 . This study failed to find evidence of HPV transcript in the two HPV positive breast cancer samples examined.…”
mentioning
confidence: 99%